Mexican Onyx Waste as Active Material and Active Material’s Precursor for Conversion Anodes of Lithium Ion Batteries - Quiroga-González, Enrique; Morales-Merino, Emma (Frontiers in Energy Research, 2021)
For the first time a limestone has been used as active material or active material’s precursor for electrodes of Li ion batteries. Limestones are very abundant, what is a condition for a sustainable development of energy storage devices. Mexican onyx has been used as a model of limestone for this work, mainly composed of calcite (calcium carbonate). Waste powder of this material from handcraft production was used, reducing costs. The material was carbonized and pyrolyzed, producing calcium oxide covered with carbon. Mexican onyx either treated or untreated works well as anode material for Li ion batteries, storing charges by conversion. Despite the grains of this material were as big as 50 m, the material with no treatment showed a maximum Li storage capacity of 530.16 mAh/g at C/3.3, while the pyrolyzed one showed a relatively stable capacity of 180 mAh/g at a relatively high charging rate of 2.7C.